2004
DOI: 10.1097/01.shk.0000129199.30965.02
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling: Toward an Application in Sepsis Diagnostics

Abstract: Sepsis is a common and serious health problem whereby improvements in diagnosis are crucial in increasing survival rates. To test whether profiling transcription is applicable to sepsis diagnosis, we analyzed whole blood using a microarray containing probes for 340 genes relevant to inflammation. The patient's gene expression pattern was highly homogenous, resulting in 69% of differentially expressed genes. With a positive predictive value of 98%, a list of 50 differentially expressed genes was compiled, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…Moreover, patients with culture-proven sepsis overexpressed TNF-a network included differentially expressed cytokines that play an important role in sepsis. 12,15,24 To our knowledge, this is the first study that has used GWEPs to evaluate the usefulness of gene expression profiles for the diagnosis of sepsis in VLBW infants. Moreover, GWEP were performed in only 0.5 mL of whole blood, which enhances applicability for the newborn period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with culture-proven sepsis overexpressed TNF-a network included differentially expressed cytokines that play an important role in sepsis. 12,15,24 To our knowledge, this is the first study that has used GWEPs to evaluate the usefulness of gene expression profiles for the diagnosis of sepsis in VLBW infants. Moreover, GWEP were performed in only 0.5 mL of whole blood, which enhances applicability for the newborn period.…”
Section: Discussionmentioning
confidence: 99%
“…13 Genome-wide expression profiles (GWEPs), however, have been successfully used for the diagnosis of sepsis and patient stratification based on the severity of septic shock in the pediatric and adult populations. [14][15][16][17] Furthermore, gene expression patterns have differentiated children with acute infections caused by respiratory viruses and Gram-positive and Gram-negative bacteria. 18 To our knowledge, no GWEP for the diagnosis of bacterial sepsis in preterm infants have been conducted.…”
mentioning
confidence: 99%
“…Accordingly, there are ongoing efforts to discover diagnostic biomarkers for sepsis (SIRS secondary to infection), and microarray approaches have the potential to enhance these efforts. Several investigators have reported genome-level signatures that can distinguish patients with SIRS from patients with sepsis [26,29,31,48]. A substantial amount of work, including validation, remains to be done in order to leverage these datasets into clinically applicable diagnostic biomarkers, but the datasets nonetheless provide a foundation for the derivation and development of diagnostic biomarkers for sepsis.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…Changes in gene expression after stimulation have been experimentally studied in human circulating leukocytes (161), DCs (162,163), and differentiated human macrophages (164) and in several animal models (165)(166)(167). Recent studies took advantage of this approach to assess whether it could successfully be applied to the differentiation between sterile systemic inflammation and sepsis in ICU patients (168)(169)(170).…”
Section: Toward a Genomic Approachmentioning
confidence: 99%